Accelerating sample preparation through enzyme‐assisted microfiltration of Salmonella in chicken extract. (7th October 2015) - Vibbert, Hunter B.; Ku, Seockmo; Li, Xuan; Liu, Xingya; Ximenes, Eduardo; Kreke, Thomas; Ladisch, Michael R.; Deering, Amanda J.; Gehring, Andrew G.
Abstract : Microfiltration of chicken extracts has the potential to significantly decrease the time required to detect Salmonella, as long as the extract can be efficiently filtered and the pathogenic microorganisms kept in a viable state during this process. We present conditions that enable microfiltration by adding endopeptidase from Bacillus amyloliquefaciens to chicken extracts or chicken rinse, prior to microfiltration with fluid flow on both retentate and permeate sides of 0.2 μm cutoff polysulfone and polyethersulfone hollow fiber membranes. After treatment with this protease, the distribution of micron, submicron, and nanometer particles in chicken extracts changes so that the size of the remaining particles corresponds to 0.4–1 μm. Together with alteration of dissolved proteins, this change helps to explain how membrane fouling might be minimized because the potential foulants are significantly smaller or larger than the membrane pore size. At the same time, we found that the presence of protein protects Salmonella from protease action, thus maintaining cell viability. Concentration and recovery of 1–10 CFU Salmonella/mL from 400 mL chicken rinse is possible in less than 4 h, with the microfiltration step requiring less than 25 min at fluxes of 0.028–0.32 mL/cm 2 min. The entire procedure—from sample processing to detection by polymerase chain reaction—is completed in 8 h. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1551–1562, 2015